KONSEP RASIONALITAS KONSUMSI MUSLIM - Novika, Aulia; Bawono, Anton (Universitas Mathla’ul Anwar Banten, 2026)
Era of globalization has reshaped the consumption patterns of Muslim communities. This study aims to examine the rationality of Muslim consumption from the perspective of Islamic economics, particularly through the principle of halalan thayyiban. A qualitative approach was employed, relying on a literature review of recent journals and reports on Islamic economics. The findings indicate that modern Muslim consumers consider not only economic factors but also spiritual, moral, and social values when making consumption decisions. The principle of halalan thayyiban serves as a standard of Islamic rationality, balancing worldly needs with spiritual orientation. Nevertheless, the implementation of this principle faces challenges from consumerist culture, social media influence, and limited access to information within households. Awareness of religious values, nutritional literacy, and social support are crucial for maintaining consistency in Islamic consumption practices. This study recommends adopting a new paradigm for evaluating Muslim consumption rationality that emphasizes welfare, ethical integrity, and spiritual blessing.